Ocena stanu i rozwoju bezpośrednich inwestycji zagranicznych (w województwie podkarpackim) - Filip, Paulina; Grzebyk, Mariola (The Analysis of State and Development of Direct Foreign Investments in Podkarpackie Voivodship, 2005)
Since the beginning of the transformation process, foreign investor interest in Poland has steadily grown. There are many attractive reasons for investing in the country like labour costs, staff qualifications, potential of the population. The potential of the Polish market is recognized as one of the most important reasons for locating new investments in the Podkarpackie. The province is situated on a major communication's cross-roads that can positively influence conditions for its development. Other good reasons for locating new investment in the Podkarpackie include the willingness of local companies to co-operate with foreign business, investment incentives. In Podkarpackie new investments are located all the time, so the list of investors lengthens every year.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 203-209